2017
DOI: 10.3389/fnagi.2017.00125
|View full text |Cite
|
Sign up to set email alerts
|

Aging Modulates the Hemispheric Specialization during Word Production

Abstract: Although older adults exhibit normal accuracy in performing word retrieval and generation (lexical production; e.g., object naming), they are generally slower in responding than younger adults. To maintain accuracy, older adults recruit compensatory mechanisms and strategies. We focused on two such possible compensatory mechanisms, one semantic and one executive. These mechanisms are reflected at inter- and intra-hemispheric levels by various patterns of reorganization of lexical production cerebral networks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 110 publications
(138 reference statements)
2
18
0
Order By: Relevance
“…Older adults also showed a greater frequency of verbal automatisms. These findings are consistent with previous studies (Bherer et al, 2004 ; Zelazo et al, 2004 ; Huizinga et al, 2006 ; Collette and Salmon, 2014 ; Baciu et al, 2016 ; Boudiaf et al, 2016 ; Hoyau et al, 2017 ) showing a generally lower cognitive performance in the course of normal aging.…”
Section: Discussionsupporting
confidence: 92%
“…Older adults also showed a greater frequency of verbal automatisms. These findings are consistent with previous studies (Bherer et al, 2004 ; Zelazo et al, 2004 ; Huizinga et al, 2006 ; Collette and Salmon, 2014 ; Baciu et al, 2016 ; Boudiaf et al, 2016 ; Hoyau et al, 2017 ) showing a generally lower cognitive performance in the course of normal aging.…”
Section: Discussionsupporting
confidence: 92%
“…Examples of increased brain FC with regions belonging to the same functional network but typically not recruited by younger adults have also been detected using lexicosemantic tasks (Agarwal, Stamatakis, Geva, & Warburton, 2016;Hoyau et al, 2018;La et al, 2016;Marsolais, Perlbarg, Benali, & Joanette, 2014;Muller, Mérillat, & Jäncke, 2016). Some studies of word production have reported BOLD signal increases in parietal, frontal, or temporal regions with age (e.g., Hoyau et al, 2017;Meunier, Stamatakis, & Tyler, 2014), as well as contralateral recruitment (e.g., La et al, 2016;Meinzer et al, 2012). Along with an impact of age, effects of behavioral performance and task demand are also expected: A recent meta-analysis focusing on semantic cognition and aging (Hoffman & Morcom, 2018) concluded that augmented activation was principally observed when older adults performed worse than younger adults, for example, during tasks drawing on executive functions.…”
Section: Introductionmentioning
confidence: 98%
“…Although older individuals often complain about proper name retrieval (Condret-Santi et al, 2013), they often obtain accuracy scores similar to those of younger adults when naming pictures of common names. Yet, this typically occurs at the expense of longer response times (Baciu et al, 2016;Hoyau et al, 2017;Wierenga et al, 2008) in possible relation with a general slowing in information processing (Feyereisen, Demaeght, & Samson, 1998). The dissociation between time and accuracy makes this task particularly interesting, as it suggests that older adults engage in adaptive mechanisms to perform it adequately.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by Fedorenko and Thompson-Schill ( 2014 ), cognitive control is sometimes necessary and useful for successful language comprehension. According to this view, cognitive control resources would be implicated in preventing language loss in healthy aging (Wingfield and Grossman, 2006 ; Hoyau et al, 2017 ). In sum, in the context of learning and rehabilitation, effortful cognitive processing may involve greater executive resources allocation, thus shedding light on the flexible and dynamic way in which cognitive control and language systems interact under high-level semantic processing.…”
Section: Discussionmentioning
confidence: 99%